Investigation and Comparison of Some Laboratories in Terms of Occupational Health and Safety by ELMERI Observation Method - Orkun Dalyan; Mehmet Pişkin; Ömer Faruk Öztürk; Nuray Özkaya (Journal of Advanced Research in Natural and Applied Sciences)
Laboratories are classified as dangerous as workplaces and contain various risk factors that may cause work accidents. For this reason, studies to reduce the dangers should be conducted in the laboratory by complying with the corrective and preventive activities specified in the relevant regulation. In the study, a survey was conducted for three laboratories in three different cities using the checklist of the relevant ministry. The survey data were applied with the ELMERI observation method and the safety indexes of the laboratories were created. According to the data obtained from the ELMERI safety index, the necessary measures to be taken in the laboratories were determined and recommendations were made.According to this research, average index values of laboratories according to categories; training and information 96%, diseases and accidents 94%, biological factors 86%, physical factors 82%, ergonomics 81%, machinery and hand tools 78%, personal protective equipment 75%, waste management 72%, electricity 71%, chemical factors 69%, fire-explosion and emergencies 67%, psychosocial factors 67%, storage 64% and general workplace layout 62%.Although there are occupational safety evaluation studies in the literature using the checklists published by the relevant ministry, there is almost no work to create safety indexes for workplaces by combining the relevant lists with the ELMERI observation method. It is suggested that the study will shed light on and form a source for future studies on laboratory safety and ELMERI observation method, especially in the laboratories where research was conducted.